2017
DOI: 10.3389/fpls.2017.01206
|View full text |Cite
|
Sign up to set email alerts
|

Antarctic Moss Multiprotein Bridging Factor 1c Overexpression in Arabidopsis Resulted in Enhanced Tolerance to Salt Stress

Abstract: Polytrichastrum alpinum is one of the moss species that survives extreme conditions in the Antarctic. In order to explore the functional benefits of moss genetic resources, P. alpinum multiprotein-bridging factor 1c gene (PaMBF1c) was isolated and characterized. The deduced amino acid sequence of PaMBF1c comprises of a multiprotein-bridging factor (MBF1) domain and a helix-turn-helix (HTH) domain. PaMBF1c expression was induced by different abiotic stresses in P. alpinum, implying its roles in stress responses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 57 publications
0
29
0
Order By: Relevance
“…The application of acetic acid increased the expression of various stress response and stress tolerance-related genes, such as heat shock family proteins, HSP20 (Muthusamy et al, 2017), HSP21 (Zhong et al, 2013), HSP70 (Tang et al, 2016; Leng et al, 2017) and HSP90 (Krishna and Gloor, 2001), ER stress-related gene, HOP3 (At4g12400; Fernández-Bautista et al, 2017a,b), catalase 1 and catalase 2 (Zou et al, 2015), multiprotein-bridging factor 1c gene ( MBF1c ; Alavilli et al, 2017), and an outer membrane tryptophan-rich sensory protein (TSPO) (Guillaumot et al, 2009). HSP20 and HSP70 family members function as molecular chaperones and help plants adapt to environmental stress (Tang et al, 2016; Leng et al, 2017; Muthusamy et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The application of acetic acid increased the expression of various stress response and stress tolerance-related genes, such as heat shock family proteins, HSP20 (Muthusamy et al, 2017), HSP21 (Zhong et al, 2013), HSP70 (Tang et al, 2016; Leng et al, 2017) and HSP90 (Krishna and Gloor, 2001), ER stress-related gene, HOP3 (At4g12400; Fernández-Bautista et al, 2017a,b), catalase 1 and catalase 2 (Zou et al, 2015), multiprotein-bridging factor 1c gene ( MBF1c ; Alavilli et al, 2017), and an outer membrane tryptophan-rich sensory protein (TSPO) (Guillaumot et al, 2009). HSP20 and HSP70 family members function as molecular chaperones and help plants adapt to environmental stress (Tang et al, 2016; Leng et al, 2017; Muthusamy et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…It is plausible to suggest that acetic acid treatment enhances drought avoidance in cassava through the regulation of the ER stress response. Overexpression of P. alpinum multiprotein-bridging factor 1c gene ( PaMBF1c ) enhanced salt tolerance in Arabidopsis (Alavilli et al, 2017). Catalase plays an important role in ABA- and H 2 O 2 -mediated signal transduction and in maintaining H 2 O 2 homeostasis in response to drought (Zou et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…However, our recent study demonstrated that Arabidopsis deficient in CNGC2 showed a higher accumulation of MBF1c protein under heat stress during the seedling stage, suggesting that CNGC2-dependent Ca 2+ signaling and ROS regulatory systems might regulate MBF1c pathways [ 44 ]. The integration of MBF1c and Ca 2+ signaling could also be supported by a recent study showing that the overexpression of Antarctic moss MBF1c in Arabidopsis plants resulted in enhanced salt tolerance, accompanied by the activation of ROS-scavenging systems, maintenance of Adenosine triphosphate (ATP) homeostasis, and facilitation of Ca 2+ signaling [ 55 ]. These findings indicate the existence of a complex network involving MBF1c, hormone signals, Ca 2+ signals, and ROS regulatory systems.…”
Section: Cross-talk Between Ros and Other Signals Involved In The mentioning
confidence: 94%
“…In the H or HN lines, MBF1C and DREB2A were targeted and showed an obviously improved expression (Figure ). AtMBF1c expression was highly induced by heat treatment, and the overexpression of AtMBF1c , TaMBF1c (the homolog of AtMBF1c in wheat) and PaMBF1c (the homolog of AtMBF1c in Polytrichastrum alpinum ) improved the drought and heat tolerance of plants (Suzuki et al ., ; Qin et al ., ; Alavilli et al ., ). It has been shown that MBF1C acts between the TF bZIP and TATA‐box binding protein (TBP) (Takemaru et al ., ), and parts of the TF bZIP (such as AtbZIP28) coordinated with the TF Hsfs, which in turn stimulated the expression of HSP genes (Kataoka et al ., ).…”
Section: Discussionmentioning
confidence: 99%